2018
DOI: 10.1111/jmp.12389
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of zoonotic importance observed in the wild, urban, and captive populations of non‐human primates in Malaysia

Abstract: Background A study was undertaken to determine gastrointestinal (GI) parasites commonly found in Malaysia's non‐human primates (NHP) living in three different types of populations (wild, urban, and captive) and the basis of major GI parasites of zoonotic importance. Methods A total of 308 samples was collected and microscopically screened from the NHP in the wild (n = 163), urban (n = 76), and captive (n = 69) populations. The samples were taken from 12 species of local NHPs. Results At least, 44 species of GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…A study in Bali, Indonesia, suggested gastrointestinal parasite burden in human populations are associated with the amount of anthropogenic land use in the surrounding communities and the participate in exposure risk behaviours with the surrounding macaques . As most of the helminths reported here are of zoonotic concern, these working macaques may pose as a source of infestation to their owners and caretakers …”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…A study in Bali, Indonesia, suggested gastrointestinal parasite burden in human populations are associated with the amount of anthropogenic land use in the surrounding communities and the participate in exposure risk behaviours with the surrounding macaques . As most of the helminths reported here are of zoonotic concern, these working macaques may pose as a source of infestation to their owners and caretakers …”
Section: Discussionmentioning
confidence: 81%
“…However, the owner may not be alert on the possible risk of transmission of malaria and filariasis from their macaques due to awareness and knowledge of the diseases in general is lacking among this endemic community . To date, little is known about the prevalence of parasitic infestations in this special group of captive primates in the households, primarily in Kelantan, Malaysia . The parasite prevalence of these working macaques is hypothesised to be higher than reported at a zoo in Malaysia .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations